Online Learning System of Learning Mathematics at SMAN 1 Kampar Kiri Hilir: Learning Difficulties Analysis Study - Abdurrahman; Maharani Eka Luckyta Sari (Mathematics Research and Education Journal, 2022)
This study aims to determine the factors behind the literacy difficulties of undergraduate mathematics in online literacy at SMAN 1 Kampar Kiri Hilir. The subjects in this study were class XI wisdom students at SMAN 1 Kampar Kiri Hilir for the academic year 2021/2022 and class XI wisdom students with a population of 68 ulama consisting of 15 male and 53 female scholars. This form of exploration is descriptive qualitative. The data collection method in this study was carried out using a check system, videlicet, by distributing online questionnaires through Google Forms which were transferred via WhatsApp Group. Based on the study results, it can be concluded that online literacy is carried out. Overall, there are 50 who find it difficult in the online tutoring and literacy process. 48.53 students find it difficult in the network aspect of sharing in the online tutoring and literacy process, 41.18 students have difficulty in the high order when sharing in the online learning process. In tutoring and online literacy, 45,59 students have difficulty understanding the material guided by school teachers, 92,65 students have difficulty installing communication either in the form of laptops or androids, 80,88 students have difficulty communicating with teachers